ANALYSIS OF SECURITY AND FRIENDSHIP TREATY BETWEEN TURKEY AND IRAN ON 22th APRIL 1926 IN TERMS OF REGIONAL SECURITY (IN ACCORDANCE WITH TURKISH AND BRITISH ARCHIVAL DOCUMENTS) - Dilşen İnce Erdoğan (Fırat University, 2019)
Iran and Turkey were key countries in the Middle East with nominal geographic location. Iran, is both a culturally and economically powerful country, is one of the main actors in the Middle East politics. It is not right to say that Turkish-Iranian relations have continued in a friendly way during history, but this situation began to change after the First World War. Britain and Soviet Russia which were imperialist counties during the First World War, attacked to Turkey and Iran. After the First World War, the terms of Nationalities and Independence were emphasis on both political and economic field in both countries which were disintegrated and occupated by the secret treaties at that time. National and ındependent states were established in Turkey by the leadership of Mustafa Kemal and by Rıza Shah in Iran. After National Struggale with emperialist, Turkey was signed agreements with Azerbaijan, Georgia and Armenia on October 13, 1921, with Afghanistan on March 1, 1921 and with Soviet Russia on March 16, 1921on the framework her foreign policy which was based on peace and friendship with neighbours. All these treaties were distrupted especially to Britain, was the main actor of this region, started to believe to decrease his sovereignity in this area. After Soviet Russia signed another treaty with Iran on February 26, 1921, the unrest of Britain increased even more. While the competition between Soviet Russia and Britain increased in the Caucasus, important problems come in to begin in the Turkısh-Iranian relations. Due to uprisings in this region, border issues had begun to rise between two countries. Despite of these negative actions, Turkey and Iran had taken some steps to develop relations since 1921, but it was not possible to create an atmosphere of trust between Turkey and Iran. In spite of these circumstances, all efforts since 1921 provided a sense of trust between the two countries in 1926. Therefore on April 22, the 1926 Security and Friendship Treaty was signed in Tehran between Turkey’s Tehran ambassador Memduh Şevket and Iranian Grand Vizier Mehmet Ali Furugi. This treaty is an important step in the development of Turkey-Iran relations.